ANALISIS PENGARUH PENERAPAN TOTAL QUALITY MANAGEMENT DAN JUST IN TIME PADA INDUSTRI MANUFAKTUR (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR DI BOGOR DAN TANGERANG) - Cynthia Maharani, Linda Santioso, (Jurnal Ekonomi, 2015)
As we know the main value to be achieved by a company is to meet the desires of its customers. Total Quality Management represents the creation of value by basing on the quality provided to consumers, while the Just In Time creating value based on a given speed. Manufacturing industry is an industry that is becoming an important part of the national economy, but some manufacturing companies in Indonesia implementing TQM and JIT just still a concept. This study tries to analyze the impact of the implementation of Total Quality Management and Just In Time for Delivery Performance. The variables used in  this  study include  Total  Quality Management  and  Just  In  Time  as  anindependent variable, and Delivery Performance as the dependent variable. The research methodology used in this study is a survey method using a questionnaire as a data collection tool. This study used a sample 6 manufacturing company located in Bogor and Tangerang. The results of the analysis using regression model showed that Total Quality Management and Just In Time has a significant impact on Delivery Performance.